Perspectives of Students and Teachers Form Continuing Professional Development: Challenge And Obstacle - Kartika Chrysti Suryandari; Rokhmaniyah Rokhmaniyah; Wahyudi Wahyudi (STAI Hubbulwathan Duri, 2024)
Continuous professional development (CPD) for teachers is crucial for enhancing their professional capabilities, particularly in pedagogical skills. Despite its importance, several barriers and challenges impede the effective development of the teaching profession. This study aims to investigate these obstacles through the perceptions of elementary school students and teachers, providing insights into the current state of CPD in education. A survey method was used to gather data from 150 participants, including students and teachers, to explore their perceptions of CPD. The survey focused on various aspects of CPD, including educational practices, learning processes, professional development activities, and supporting mechanisms. The findings revealed significant differences in perceptions between students and teachers across the examined aspects. Teachers predominantly prioritized the learning process in their professional development efforts. Major obstacles identified included a lack of motivation and insufficient intervention for practicing teachers. Additionally, a critical challenge for teachers was the deficiency of high-quality resources necessary to conduct effective research in learning methodologies. The disparity in perceptions between students and teachers highlights the need for more targeted CPD programs that address the specific needs of educators. Enhancing motivation and providing adequate support and resources are essential for overcoming these barriers. Addressing these challenges can lead to more effective teaching practices and ultimately improve the quality of education. This study underscores the importance of understanding the barriers and challenges to CPD from both students' and teachers' perspectives. By prioritizing the learning process and addressing motivational and resource-related issues, stakeholders can better support the professional development of teachers, leading to improved pedagogical outcomes.